-8=y-6

Simple and best practice solution for -8=y-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8=y-6 equation:


Simplifying
-8 = y + -6

Reorder the terms:
-8 = -6 + y

Solving
-8 = -6 + y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1y' to each side of the equation.
-8 + -1y = -6 + y + -1y

Combine like terms: y + -1y = 0
-8 + -1y = -6 + 0
-8 + -1y = -6

Add '8' to each side of the equation.
-8 + 8 + -1y = -6 + 8

Combine like terms: -8 + 8 = 0
0 + -1y = -6 + 8
-1y = -6 + 8

Combine like terms: -6 + 8 = 2
-1y = 2

Divide each side by '-1'.
y = -2

Simplifying
y = -2

See similar equations:

| 8(n-3)-(2-n)= | | 5[h+2]=3[j-1] | | 3x(X+1)-3x= | | -9+w=-7 | | 4x+-9+-9y=6 | | -9=u+9 | | .5(100+A)=50 | | x(-53-15x)=0 | | 6+2(3e-1)= | | 29=-2(4x-5)+3(3x+6) | | 2-12x+6=0 | | 4x-7=2b+X | | 12p-7=8p+9 | | 16=2y-12 | | 11x-3=5x+5 | | 2g-3-3G-5=1 | | 40000*X=1550000 | | 51+7t=0 | | 9y=3+7x | | 34-4x=7-7x | | 3=5x-5 | | 17p+13q+p-5q-5p= | | 17p+13q+p+5q-5p= | | 16+5=7x | | 1=5x-5 | | 4w+17=93 | | -2=5x-5 | | 16a+16b+2c+2c-5b-4a= | | 8=9x+3 | | 32-8a=52-6a+2 | | -3=5x-5 | | (7x+3)-2=22 |

Equations solver categories